Balay Bagaybay coconut product development center - Laylo, Roma Belle C.; Rivera, Dave V. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Lucena City, 137 kilometers southeast of Metro Manila is the Capital of Quezon Province- also hailed as "Coco palm City of the South." Aside from this, Lucena is the first and only Highly Urbanized City in the Southern Tagalog Region. However, in spite of this, Lucena remains to be highly agricultural with more than 50% of its land area is dedicated to agriculture. Instead of seeing this as a weak point of the city that is geared towards economic progress, it is considered as the asset of the city. This agricultural asset of Lucena is the major anchor point of this project. Balay Bagaybay is a model urban farming facility that caters to product development of the main product of the province -- coconut. This project revolves around the agricultural industry as stimulant of development; shifting the paradigm on designing urban cities.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman